A need for clarity on surgical management of breast sarcoma: Scottish sarcoma network guidelines and regional audit. Issue 6 (June 2021) - Lo, Steven; Foster, Naomi; Campbell, Lindsay; White, Jeff; Nixon, Ioanna; Mansell, James; McCleery, Mark; Whyte, Lynsey; Cowie, Fiona
Summary: Currently, there are no comprehensive breast sarcoma guidelines in the UK. There is therefore a need for guidelines to clarify surgical management, which we have based on data from our regional audit, current evidence, and consensus between West of Scotland Breast Cancer and Scottish Sarcoma Managed Clinical Networks. Methods and results: From 2007 to 2019, 46 patients were treated with breast sarcoma in the West of Scotland. Sarcoma Centre versus Peripheral Hospitals: Incomplete excision rate was 0% at sarcoma centre and 50% at peripheral hospitals ( p = 0.0002, Odds Ratio 43). For angiosarcoma, 0% positive margin at the sarcoma centre versus 62.5% at the peripheral unit ( p = 0.0036, odds ratio 39.3). Tumours treated at the sarcoma centre were larger than those treated at peripheral hospitals (92.5 versus 39.7 mm, p = 0.0009). WLE (wide local excision) versus mastectomy: Out of eight WLE patients, seven (87.5%) had positive margins, with 6 of these patients proceeding to mastectomy (i.e. 75% WLE patients ultimately had a mastectomy). The positive margin rate was significantly higher in WLE (87.5%) than in mastectomy (10.3%) ( p = 0.0001, odds ratio 60.7). Survival: No difference was noted between the sarcoma centre and peripheral hospitals for overall survival ( p = 0.43), stratified for tumours <5 cm ( p = 0.16), and disease-free survival ( p = 0.45). Conclusions: Our data strongly suggest that specific guidelines are needed for breast sarcoma, and that managing these patients according to breast carcinoma protocols in peripheral hospitals is sub-optimal. We recommend centralisation of breast sarcoma patient care to a specialist sarcoma centre, with WLE not recommended as a firstline surgical option given both the high rates of incomplete excision and subsequent need for completion mastectomy.